Forecast intervals for US/EURO foreign exchange rate - Mihaela Simionescu (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2017)
The main goal of this research is to construct and assess forecast intervals for monthly US/EURO foreign exchange rate. The point forecasts used to build the intervals are based on a vector autoregression (VAR model) and on a Bayesian VAR model for data starting with the first month of 1999. The forecast intervals are based on the prediction error of the previous month. All the interval predictions based on VAR model included the actual values from 2014. The probability that the intervals based on BVAR model include the registered values of exchange rate is less than 0.8, according to likelihood ratio and chi-square tests.
Keywords: C51; C53; 330; forecast intervals; exchange rate; VAR model; Bayesian VAR model